Comparação da produtividade do cultivar de tomate ’Alcobaça’ com três cultivares do tipo ’Santa Cruz’, na Baixada Fluminense - Rocha Leal, Nilton (Revista Ceres, 2025)
The present study was conducted in 1969 at Instituto de Pesquisa Agropecuária do Centro-Sul — IPEACS —, located at Baixada Fluminense. The main purpose of the study was to compare the yielding hability of the tomato variety ’Alcobaça’ with three Brazilian varieties.